2019
DOI: 10.1155/2019/3508658
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng Inhibits Metabolism of Diester Alkaloids by Downregulating CYP3A4 Enzyme Activity via the Pregnane X Receptor

Abstract: To investigate the effects of P. ginseng C.A. Mey (P. ginseng) on the metabolism of diester alkaloids and explore the potential mechanism. P. ginseng was administered orally to rats for 7 days, after which liver microsome samples were prepared and then incubated with diester alkaloids. Ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry was used to determinate the concentration of diester alkaloids to calculate the clearance rate. The cocktail method was used to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Some studies have shown that Chinese herbal ingredients in Si Jun Zi decoction influence CYP450 enzymes. A study [11] showed that ginseng reduced the CL of midazolam and caffeine, which were metabolized by CYP450 enzymes. CYP3A2 (an isozyme of CYP3A4) and gene expression levels in Sprague-Dawley rats exposed to P. ginseng extracts were evaluated by western blotting and quantitative PCR in the study [11] and compared with the control groups, P. ginseng downregulated the expression of CYP3A2 at both the protein and gene levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have shown that Chinese herbal ingredients in Si Jun Zi decoction influence CYP450 enzymes. A study [11] showed that ginseng reduced the CL of midazolam and caffeine, which were metabolized by CYP450 enzymes. CYP3A2 (an isozyme of CYP3A4) and gene expression levels in Sprague-Dawley rats exposed to P. ginseng extracts were evaluated by western blotting and quantitative PCR in the study [11] and compared with the control groups, P. ginseng downregulated the expression of CYP3A2 at both the protein and gene levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study [11] showed that ginseng reduced the CL of midazolam and caffeine, which were metabolized by CYP450 enzymes. CYP3A2 (an isozyme of CYP3A4) and gene expression levels in Sprague-Dawley rats exposed to P. ginseng extracts were evaluated by western blotting and quantitative PCR in the study [11] and compared with the control groups, P. ginseng downregulated the expression of CYP3A2 at both the protein and gene levels. Another study [12] indicated that repeated administration of Sailuotong induced CYP1A2 and CYP2C11 but significantly inhibited CYP3A1/3A2 in rats, and these impacts were attributed to the ingredients of ginseng and gingko individually or cooperatively to a large extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginseng (Panax notoginseng) has the best combination effect with Aconitum , in terms of detoxification and enhancing drug action. In vitro experiment has shown that Ginseng could reduce the metabolism of DDAs through inhibition of CYP3A4 expression and activity [ 79 ]. In a rat model, Ginseng could slow down the metabolisms of DDAs from Fuzi when given orally [ 80 ].…”
Section: Detoxification Of Aconitum In Traditional and Modern Waysmentioning
confidence: 99%